Unsur Arab dan Islam dalam Pertunjukan Wayang Kulit - Sangidu, Sangidu; Iwan, Cecep Darul (Research and Development Institution, Darussalam Institute for Islamic Studies, 2017)
Sunan Kalijaga is a very creative figure in preaching for the spread of Islam. One of the media utilized by Sunan Kalijaga in preaching is to show wayang kulit. Wayang kulit at that time is very popular by rural communities or urban communities. For that, the mission carried out by Sunan Kalijaga crowded by the visitors and they want to convert to Islam. He argues that in preaching the most important is the quantity first, while the quality for a while has not worked. Thus, wayang kulit is one of the dakwah media that is powerful enough to attract people so that they flock to Islam.